Exploring Essential Oils: Extraction, Biological Roles, and Food Applications - Nitu Rani; Vinay Kumar; Arjun Chauhan (Journal of Food Quality)
Essential oils (EOs) are volatile, naturally occurring complex compounds extracted from aromatic plants. EOs are secondary metabolites of aromatic herbs or plants that contain strong odors. They are typically extracted through methods like hydrodistillation and steam distillation, as well as modern techniques such as supercritical fluid extraction (SFE) and ultrasound-assisted extraction (UAE), which enhance efficiency and ensure high product quality. Since medieval times, EOs have been extensively employed for their biological activities. Today, they are prevalent in pharmaceutical, sanitary, cosmetic, agricultural, and food industries. Their Generally Recognized as Safe (GRAS) status has sparked significant interest in their use for food preservation, aligning with consumer trends favoring eco-friendly alternatives over synthetic chemical preservatives. EOs offer a range of food applications, including food preservation, flavor enhancement, and active packaging. EOs play a crucial role not only in extending the shelf life of perishable foods but also in enhancing sensory attributes and controlling microbial spoilage. Despite their growing popularity, the application of EOs is sometimes limited due to potential adverse effects. However, they continue to be powerful agents for maintaining food safety, prolonging shelf life, and meeting consumer demands. Integrating EOs into active packaging materials extends shelf life and enhances safety, while nanoencapsulation techniques help mitigate issues related to their strong odor and volatility. Navigating the regulatory landscape surrounding EOs in food products requires strict adherence to safety guidelines to ensure consumer well-being. This review delves into the intricate world of essential oils, exploring their origins in aromatic and medicinal plants, various extraction techniques, diverse biological roles, applications in the food industry, and associated regulatory concerns.